Implicit and explicit attitudes among students - Felix Neto (2009)
Mental processing and mental experience is not the same thing. The former is the operation of the mind; the latter is the subjective life that emerges from these operations. In social evaluation, implicit an I explicit attitudes express this distinction. https://implicit.harvard.edu/ was created to provide experience with the Implicit Association Test (IAT) a procedure designed to measure social knowledge that may operate outside of awareness. In this paper we examined the relationships between the implicit Association Test, and explicit measures. One hundred and forty three Psychology college students from University of Porto completed measures for this study. Results suggest that (a) implicit preferences are pervasive, and (b) implicit and explicit attitudes are weakly related.